Neonatal nursing efficacy: practical standards of nursing care provision in a newborn network. (4th April 2011) - Pillay, T; Nightingale, P; Owen, S; Kirby, D; Spencer, S A
Abstract : Aims: To measure the nursing workload and timely completion of essential tasks in relation to BAPM1 recommended staffing levels in a Newborn Network. Methods: A prospective observational study was conducted by measuring the time taken by selected nurses in our Newborn Network to undertake necessary tasks for babies receiving different levels of care. A single independent assessor observed and assessed the time spent on various tasks at each of the six constituent neonatal units of our Newborn Network. The individual workload for each nurse was evaluated against BAPM standards of nursing workload. Note was made of how long essential pre-determined tasks were delayed. The impact on the quantity of care given and on the number of delayed tasks was compared between those with the recommended workload or less and those that were overstretched. Results: Between October 2008 and February 2009 89 nurses from six units were observed caring for 244 neonates over 534 h. 54% of nursing shifts failed to meet BAPM standards. These shifts demonstrated a 26% decrease in clinical care provided. Time taken on nursing breaks (average 20 min, 95% CI 3) was 51.4% less than allocated. 92(17%) essential tasks were delayed >1 h or not done. Delays/omissions were more likely to occur when BAPM standards were not met (53% vs 40%, p=0.05). In 43 nursing observations without delays/omissions, 302 min was spent on clinical care per neonate in Intensive Care (IC), 254 in High Dependency Care (HDC) and 158 in Special Care (SC). This indicates that a nurse cannot care for >1.2, 1.4 and 2.3 babies in IC, HDC and SC respectively without delaying treatment. Conclusion: Understaffing leads to measureable problems including delays to essential treatment, reduced clinical care and absent staff breaks. The BAPM standards are not aspirational and should be regarded as a minimum.